Corporate Social Responsibility and Firm Performance: Evidence from the COVID-19 - Chen, YH (2022)
The relationship between corporate social responsibility (CSR) and corporate performance has been a controversial topic. The COVID-19 pandemic raised a great deal of public interest in CSR and provided a special opportunity for research related to CSR. This study evaluates the impact of CSR on corporate performance in the context of the COVID-19 pandemic. Result shows that the impact of CSR on corporate performance during COVID-19 is negative. Using difference-in-differences (DID) regression, this study finds that CSR companies experienced a significant negative decline in corporate performance during COVID-19, suggesting that CSR activities during this crisis period resulted in overinvestment. The estimation of the dynamic treatment effects suggests that the negative impact caused by CSR was dynamically sustained in the post-COVID-19 crisis period. This study further shows that such negative impact is only significant among large CSR firms. This study is valid for a range of robustness tests.